1994
DOI: 10.1016/s0022-5347(17)32613-7
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Vaginal Pack Test in Large Cystoceles

Abstract: To detect possible stress urinary incontinence associated with but masked by large cystoceles protruding through the vaginal orifice, a vaginal pack test was done in conjunction with video fluoro-urodynamic studies. Sixteen female patients with large cystoceles did not demonstrate stress urinary incontinence on clinical examination and were included in this study. Additionally, 10 healthy female volunteers underwent the same test to study the effect of a vaginal pack on urethral dynamics. The vaginal pack reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 10 publications
0
53
0
2
Order By: Relevance
“…Two patients presented a de novo stress urinary incontinence after previous formal repair of cystocele. Urodynamic examination including leak point pressure evaluation [15]was performed in all patients to correctly evaluate and classify SUI before and after cystocele repositioning according to Ghoniem recomendations [16]. One patient was diagnosed as having type III SUI (instrinsic sphincteric deficiency) while the others presented a type II SUI (urethral hypermobility) before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Two patients presented a de novo stress urinary incontinence after previous formal repair of cystocele. Urodynamic examination including leak point pressure evaluation [15]was performed in all patients to correctly evaluate and classify SUI before and after cystocele repositioning according to Ghoniem recomendations [16]. One patient was diagnosed as having type III SUI (instrinsic sphincteric deficiency) while the others presented a type II SUI (urethral hypermobility) before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Using the vaginal pack test for reduction of large cystoceles. Ghoniem et al found a 50% rate of type III (internal sphincteric deficiency) incontinence [14]. Lastly, 27% of patients undergoing surgical correction for their pelvic organ prolapse had coexistent genuine stress incontinence and detrusor overactivity with their prolapse reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The vesical pressure required to induce visible leakage was recorded as VLPP [6,8] . If a significant cystocele was present, a VLPP was measured with packing in the vagina in an attempt to avoid faulty elevations due to the obstructive nature of a cystocele [8,9] . A VLPP of !…”
Section: Methodsmentioning
confidence: 99%